2008
DOI: 10.1074/jbc.m709172200
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-binding Model of the Chlorophyll Biosynthetic Magnesium Chelatase BchH Subunit

Abstract: Photosynthetic organisms require chlorophyll and bacteriochlorophyll to harness light energy and to transform water and carbon dioxide into carbohydrates and oxygen. The biosynthesis of these pigments is initiated by magnesium chelatase, an enzyme composed of BchI, BchD, and BchH proteins, which catalyzes the insertion of Mg 2؉ into protoporphyrin IX (Proto) to produce Mg-protoporphyrin IX. BchI and BchD form an ATPdependent AAA ؉ complex that transiently interacts with the Proto-binding BchH subunit, at which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 46 publications
1
31
1
Order By: Relevance
“…In general terms, the energetically unfavorable reaction of insertion of Mg 2ϩ into protoporphyrin IX by the H subunit is fueled by ATP hydrolysis performed by the ID complex. The process also involves considerable conformational changes within the ID complex (15) as well as within the H subunit (7). The present study supports earlier observations that the I subunit has ATP hydrolytic activity that exceeds the ATP hydrolytic activity of the ID complex (11).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In general terms, the energetically unfavorable reaction of insertion of Mg 2ϩ into protoporphyrin IX by the H subunit is fueled by ATP hydrolysis performed by the ID complex. The process also involves considerable conformational changes within the ID complex (15) as well as within the H subunit (7). The present study supports earlier observations that the I subunit has ATP hydrolytic activity that exceeds the ATP hydrolytic activity of the ID complex (11).…”
Section: Discussionsupporting
confidence: 80%
“…Magnesium chelatase requires the presence of three gene products, BchH, BchD, and BchI (often referred to as the H, D, and I subunits), which have molecular masses of 140, 70, and 40 kDa, respectively (1)(2)(3)(4). The H subunit has been shown to bind the porphyrin substrate with high affinity (3)(4)(5)(6)(7) and has also been predicted to bind the magnesium ion substrate, by analogy with the homologous CobN, the cobalt-binding subunit of cobalt chelatase (8). Based on these observations, the H subunit has been suggested to be the catalytic component of the enzyme (3)(4)(5).…”
mentioning
confidence: 99%
“…Fig. 3 also compares the 3D models of ChlH with the apo-and porphyrin-bound structures of BchH (C and D, respectively), taken from the earlier work of Sirijovsky et al (18). The larger size of ChlH is apparent, mainly attributable to the region of ϳ100 residues indicated by the cyan bar in supplemental Fig.…”
Section: Purification and Functional Analysis Of The Chlh Protein Fromentioning
confidence: 99%
“…Single-particle EM analysis of negatively stained BchH proteins from R. capsulatus revealed a three-lobed structure at a resolution of 25 Å. Differences in the structure were noted between the apo-and Protobound forms of H, and it was suggested that both the N-and C-terminal domains were important for porphyrin binding (18). The Mg chelatase BchH subunits from the purple photosynthetic bacteria such as R. capsulatus have sequence identities of 35-40% when compared with ChlH subunits from oxygen-evolving photosynthetic cyanobacteria, algae, and higher plants, but within this latter group sequence identities of over 60 -80% are common (supplemental Table S1).…”
mentioning
confidence: 99%
“…The 150-kD subunit has been suggested to be the catalytic subunit as it binds the protoporphyrin IX substrate and most likely also the Mg 2+ substrate (Willows et al, 1996;Jensen et al, 1998;Willows and Beale, 1998;Karger et al, 2001). A structural model of Rhodobacter capsulatus BchH at 25 Å has recently been established based on electron microscopy and single-particle reconstruction (Sirijovski et al, 2008). The polypeptide folds into three lobeshaped domains connected at a central point.…”
mentioning
confidence: 99%